Improving the Services at the Outlets of McDonald’s Malaysia through Process Innovation - Chummar George, Pudussery (2014)
In 2010, the food processing industry contributed about 10% of the Malaysian manufacturing output attracted a total of RM1.972 billion in 69 projects. Employment in the processed food and beverages industry decreased in 2009 by 5.1% to 43,080 compared with 45,418 in 2008. Small and medium sized enterprises represent more than 80% of the total number of establishments in the processed food segment. In Malaysia, McDonald’s is leading the food franchisor at second place to KFC, and is planning on increasing its franchisees from currently 230 to over double during the next eight years. From evaluating the development of the business, the corporation plans on running a total of 500 restaurants by 2020 considering the demand and business potential. It is a matter of high priority for a leading player like McDonald’s to keep coming with new ideas so as to sustain in the competition and stay ahead. With it’s agenda of doubling the number of outlets in Malaysia over the coming years, it proves necessary to keep improving on a continuous basis by understanding the customer’s needs, demands and concerns, and fulfilling them as much as possible. With increasing business agenda of the corporation, it also has to keep up with the competition that it faces from existing and emerging new players, making it an overwhelming task for McDonald’s to keep up with. For this study, there are a total of five variables of which four of them are the independent variables ‘Efficiency’, ‘Quality’, ‘Customer Service’ & ‘Environment’ and the fifth variable is a dependent variable which is ‘Service Innovation’ to investigate on how the services being provided to the customers at the outlets can be made more efficient. The study was conducted from distributing survey questionnaires among the customers being served at the outlets of McDonald’s Malaysia. From conducting this study, the recommendations brought forward were mainly related to measures involving the use of technology to help in improving the processes being currently followed at the outlets. The recommendations were brought forward with the aim of satisfying the needs of the customers being served at the outlets of McDonald’s Malaysia which at the same time becomes feasible to be carried out for the corporation.